Effect of EBG with varying parameters on the regular 2.45GHZ patch antenna / Amir Khalid Shahrin Iskandar - Shahrin Iskandar, Amir Khalid (2016)
This paper presents a regular microstrip patch antenna with mushroom-like electromagnetic band gap (EBG) structures place on the antenna with varying parameters. The patch antenna is designed at the 2.45GHz frequency. The regular patch antenna is made with copper patch and FR-4 as the substrate. The FR-4 has a dielectric constant of 4.7 and substrate thickness of 1.6mm. All the simulation work is completed through the use of Computer Simulation Technology (CST) software. Simulations were carried out using CST to verify the performance of EBG structures with different parameters in patch antenna. The designs are divided into two categories that are a EBG structures with via and EBG structures without via. This work is to test whether the EBG structure placement is able to increase the performance of the regular patch antenna and at what parameters does the performance of the patch antenna improve. The result of the simulations show that the type of EBG structure placement that has been used for the simulation only improved the performance of the antenna's gain but not other antenna performance. The best antenna designed that could be fabricated has been fabricated and measured.